(untitled) - Brown, Aaron (Hoboken, N.J., 2006)
If you're looking for tips on becoming a better poker player, you've probably come to the wrong place. Brown does cover the game's basics and shares plenty of stories from his early card-playing days, which include Harvard games with the likes of Scott Turow. But he has much bigger stakes to discuss in this upbeat and entertaining guide. Drawing on his background at Morgan Stanley (where he's an executive director) and other financial institutions, Brown proposes that "finance can only be understood as a gambling game" and vice versa—and though the material can be rough going for those without some investment training, he's very convincing once all the cards are laid out. In an extended historical example, Brown shows how the economy of colonial America was jump-started by the introduction of faro dealers into French Louisiana. He sees the current financial market as filled with similar wealth-generating potential and believes "taking risks just makes sense" in such an opportunity-rich climate. Poker, then, becomes a tool for learning how to evaluate and embrace financial risk. Brown's model is instantly graspable, but so contrary to the conventional wisdom on both economics and gambling that it may well spark debate
Keywords: Stock,Finance,Cổ phần,Tài chính